Birdwatching guide : turn yourself into a birdwatching expert - Wolfson, Elissa; Kress, Stephen W.; Hume, Rob (Dk Publishing, 2025)
Start your birdwatching journey in the safe hands of a lifelong birder. Through a series of chapters, you will build from an absolute beginner, exploring your own backyard, soaking up useful tips and insights gained from years of birdwatching.